Interakcyjne łańcuchy transferu wiedzy - Perechuda, Kazimierz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the paper are presented: added value chain, material and non-material value chain, the diffusion of the explicit and tacit knowledge in the sectors of the national economy, personal barriers of the knowledge transfer, harmonization of the sellers and buyers knowledge chain. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 200-205